Frequency domain analysis and clinical outcomes of pulsatile and non-pulsatile blood flow energy during cardiopulmonary bypass. (November 2021) - Jiang, Qiliang; Sun, Jian; Xu, Lingfeng; Chang, Xin; Sun, Lin; Zhen, Yue; Guo, Zhen
Introduction: The superiority of pulsatile perfusion during cardiopulmonary bypass remains controversial. We analyzed the frequency-domain characteristics and organ protection of pulsatile and nonpulsatile flow in adult patients with valvular disease. Methods: EEP and SHE were used to calculate blood flow energy in 60 patients. The Fast Fourier Transform was employed to analyze the power spectral density and power density ratio (Rvpd) of flow energy. Changes in endothelin-1, nitric oxide, interleukin-6, 10, tumor necrotic factor, S100β, NSE, blood and urinary β2-microglobulin levels were investigated to assess the endothelial function, inflammatory reaction, kidney and brain injury during CPB. Results: EEP and SHE in PP group at each time point were 1.52–1.62 times and 2.03–2.22 times higher respectively compared with NP group. Power spectral density analysis demonstrated that the blood flow energy frequencies in each group were all within 40 Hz and the low frequency energy (0–5 Hz) was dominant in physiological perfusion (>90%). The energy ratio of 0–5 Hz at radial artery was significantly decreased compared with that of post arterial filter in PP (81% vs 64%) and NP (63% vs 37%) group. The power density ratio (Rvpd) was higher than that of NP in all frequency ranges at the radial artery (9.51 vs 4.68 vs 3.59) and arterial filter (3.87 vs 2.69 vs 2.38). The S100β, NSE Urinary and plasma β2-microglobulin level were significantly increased at 6 and 24 hours after surgery in two group, and significantly higher in group NP. Conclusion: PP provided more energy than NP. The proportion of low frequency energy in the pulsatile or nonpulsatile flow is significantly reduced. The low-frequency energy is significantly attenuated during conduction to peripheral tissues in nonpulsatile flow. The surplus pulsatile energy influences the secretion of endothelial and inflammatory factors, and demonstrate better cerebral and kidney protective effect at the biological marker level.